The development of modern industries in Bengal - Ray, Indrajit, author.
1 online resource (294 pages)
Keywords: Bengal’s traditional industries, once celebrated worldwide, largely decayed under the backwash effects of the British Industrial Revolution in the first half of the nineteenth century. Although colonial ambivalence is often cited as an explanation, this study also shows that a series of new industries emerged during this period. The book reappraises the thesis of India’s deindustrialisation and discusses the development status of the traditional industries in the early nineteenth century, examines their technology, employment opportunities and marketing and, finally, analyses the underlying reasons for their decay. It offers a study of how traditional industries evolved into modern enterprises in a British colony, and contributes to the broader discussion on the global history of industrialisation.This book will be of interest to scholars of Indian economic history as well as those who seek to understand the widespread effects of industrialisation, especially in a colonial context.